Big sky bachelor - Sims, Joanna (Love story writer) (Sims, Joanna (Love story writer) Brands of Montana, 2025)
When successful real estate broker to the rich and famous Danica Brand leaves her two-timing fiancé to regroup at the family ranch, the city girl doesn't count on a tall, handsome doctor sweeping her off her feet. Dr. Matteo Katz is the most eligible bachelor in Big Sky, Montana. And everything from his Miami good looks to his small-town hospitality temps Danica into his bed. Matteo's endgame has always been marriage and a family, but Danica is the only woman who makes him ready to commit. Can he convince her to trade her big-city lifestyle for a small-town dream and a chance to redefine her idea of "home"?